Pollen, non-pollen palynomorphs, LOI, micro- and macrocharcoal and C14 records from core Peny (Kursk region, Russia) - A Kasianova; Ekaterina Lukanina; Lyudmila S Shumilovskikh (PANGAEA, 2023)
The dataset represent pollen, non-pollen palynomorphs, LOI, micro- and macrocharcoal and C14 records from core Peny, Kursk region, Russia. The core Peny was collected in 2009 by Lyudmila Shumilovskikh, Frank Schlütz, Jens Schneeweiß and Oleg Radyush with a Russian corer. Laboratory processing for palynological studies took place in the Dep. Palynology and Climate Dynamics, Georg-August-University of Göttingen in 2009 by Lyudmila Shumilovskikh and 2020 by Alisa Kasianova. For each palynological sample, one millilitre of material was treated with hydrochloric acid, potassium hydroxide, hydrofluoric acid, acetolysis mixture, microsieved (6 μm) and stored in glycerol. Before acid, Lycopodium spores were added to calculate pollen influx. Counting was carried out by Alisa Kasianova. Standard microscopical magnification was 400 exttimes, for ambiguous objects 1000x with oil immersion. Identification and morphological pollen types follow Beug (2004) and type collections. Non-pollen palynomorphs (NPP) follow Miola (2012) and the Non-Pollen Palynomorphs Image Database (NPP ID, http://non-pollen-palynomorphs.uni-goettingen.de/). New NPP types were described and have been uploaded to the Non-Pollen Palynomorphs Image Database (NPP ID, http://non-pollen-palynomorphs.uni-goettingen.de/). In addition, pieces of burnt plant fragments of > 50 μm were counted. Laboratory processing for macrocharcoal took place in the Dep. Palynology and Climate Dynamics, Georg-August-University of Göttingen in 2020 by Alisa Kasianova. These samples were treated in the laboratory in Sodium Hexametaphosphate and in bleach, living overnight after each treatment and followed by sieving through 125 μm sieve, and eventually counting of charcoal particles under a binocular microscope under 10 exttimes to 15 exttimes magnification. Samples for loss-on-ignition was processed by Ekaterina Lukanina in 2021. Samples (1 ml) were obtained at 2 cm intervals (44 samples). LOI samples were oven-dried for 22 hours at 105 °C, for 4 hours at 550 °C and for 2 hours at 950 °C (Dean 1974; Heiri et al. 2001). LOI records are given as percentages. For an absolute chronology, bulk samples, macroremains and pollen were dated by the radiocarbon laboratories of Poznan (Poland) and Erlangen (Germany).